Stimulus Control Research and Practice: Considerations of Stimulus Disparity and Salience for Discrimination Training - Halbur, Mary E. (Behav Anal Pract, 2021)
Stimulus control plays a prominent role in behavior-analytic service delivery, as many discrimination skills are necessary for daily interactions. Clarification and standardization of terminology are necessary for the advancement of research and practice on stimulus control. The purpose of the present article is to provide an overview of stimulus control and discrimination training as they relate to the disparity and salience of stimuli. An overview and examples of stimulus disparity and stimulus salience are provided, followed by recommendations for efficacious service delivery.